Exercise-induced anaphylaxis: A serious but preventable disorder - Miller, C. W. T.; Guha, B.; Krishnaswamy, G. (The Physician and Sportsmedicine, 2008)
Abstract: Described for the first time approximately 30 years ago, exercise-induced anaphylaxis is a rare disorder characterized by development of a severe allergic response occurring after mild-to-strenuous physical activity. This disorder is especially important to recognize with the recent increase in physical activity and health fitness fads. A number of predisposing factors (eg, prior ingestion of particular food groups) linked to exercise-induced anaphylaxis has been outlined over the years. Mechanisms governing the condition are still being unveiled, and it is likely that one mechanism involves mast cell degranulation and inflammatory mediator generation resulting from the biochemical effects of exercise, sometimes in the presence of an ingested allergen such that wheat or shell fish. Clinical manifestations usually occur after around 10 minutes of exercise, and follow a specific sequence, starting with pruritis and widespread urticarial lesions, evolving into a more typical anaphylactic picture with respiratory distress and vascular collapse. Fatality is exceedingly rare, with only one documented case in the literature. There is an overlap of symptoms with other syndromes (such as systemic mastocytosis and cholinergic urticaria), and these should be remembered when establishing a differential. Treatment of exercise-induced anaphylaxis consists of immediate stabilization geared toward the anaphylactic response with epinephrine and anti histamines. The patient needs to be educated on preventive measures and equipped with an epinephrine autoinjector in the event of an emergency. Exercise-induced anaphylaxis remains a potentially serious disorder, and the health care provider should be aware of its clinical features and effective management strategies.